AKT inhibition mitigates GRP78 (glucose‐regulated protein) expression and contribution to chemoresistance in endometrial cancers. Issue 1 (8th February 2013) - Gray, Michael J.; Mhawech‐Fauceglia, Paulette; Yoo, Eunjeong; Yang, Wangrong; Wu, Eijean; Lee, Amy S.; Lin, Yvonne G.
<x xml:space="preserve">Abstract</x> Overexpression of the unfolded protein response master regulator GRP78 is associated with poor prognosis and therapeutic resistance in numerous human cancers, yet its role in endometrial cancers (EC) is undefined. To better understand the contribution of GRP78 to EC, we examined its expression levels in EC patient samples and EC cell lines. We demonstrate that GRP78 overexpression occurs more frequently in EC tissues compared with that found in normal endometrium, and that GRP78 expression occurs in most EC cell lines examined. Functional analysis demonstrated that GRP78 is inducible by cisplatin in EC cells, and siRNA knockdown of GRP78 augments chemotherapy‐mediated cell death. Examination of AKT and GRP78 expression demonstrated that inhibition of AKT activity by MK2206 blocks GRP78 expression in EC cells. SiRNA studies also revealed that knockdown of GRP78 reduces but does not abrogate AKT activity, demonstrating that GRP78 is required for optimal AKT activity. In the presence of MK2206, siRNA knockdown of GRP78 does not augment AKT mediated survival in response to cisplatin treatment, suggesting that GRP78′s antiapoptosis functions are part of the AKT survival pathway. Targeted therapies that reduce GRP78 expression or activity in cancers may serve to increase the effectiveness of current therapies for EC patients.